Enhanced catalytic activity induced by the nanostructuring effect in Pd decoration onto doped ceria enabling an origami paper analytical device for high performance of amyloid-β bioassay - Cui, Kang (2022)
In this work, we fabricated a novel origami paper-based analytical device (oPAD) assisted by the nanostructuring effect of in situ Pd decoration of Cu/Co-doped CeO2 (CuCo-CeO2-Pd) nanospheres, functionalized with their strongly enhanced electrocatalytic properties to realize an electrochemical and visual signal readout system in oPAD, for highly sensitive detection of amyloid-β (Aβ). The CuCo-CeO2-Pd nanospheres were introduced as an enhanced "signal transducer layer" on account of the electron transfer acceleration caused by catalyzing glucose to produce H2O2 for differential pulse voltammetry signal readout and further 3,3'5,5'-tetramethylbenzidine (TMB) oxidation for colorimetric analysis. Meanwhile, for achieving superior performance of the proposed oPAD, in situ growth of urchin-like gold nanoparticles (Au NPs) onto cellulose fibers was adopted to improve "the recognition layer" in favor of immobilizing antibodies for targeting Aβ through specific antigen-antibody interactions. Combined with the delicate design of oPAD, exhibiting actuation of the conversion procedure between hydrophobicity and hydrophilicity on paper tabs in the assay process, the oPAD successfully enabled sensitive diagnosis of Aβ in a linear range from 1.0 pM to 100 nM with a limit of detection of 0.05 pM (S/N = 3) for electrochemical detection, providing a reliable strategy for quantifying the Aβ protein in clinical applications.